Does verb type affect action naming in specific language impairment (SLI)? evidence from instrumentality and name relation - Kambanaros, Maria (My University, 2013)
Children with specific language impairment (SLI) have particular problems using verbs. However, not much is known about how children with SLI retrieve different types of verbs. In the present study, bilectal Greek-speaking children with and without SLI were assessed on naming of different verbs held constant for argument structure but manipulated for lexical-semantic and phonological-lexical features. School-aged children with SLI as well as typically developing age- and vocabulary-matched peers named 39 colored photographs representing actions in a confrontation naming task. Stimuli included actions involving an instrument (e.g., sweeping), i.e. instrumental verbs, and actions that have a name-relation with the instrument (e.g., sawing), i.e. name-related instrumental verbs as well as actions not involving an instrument (e.g., climbing), i.e. non-instrumental verbs. Instrumental verbs were significantly more difficult to retrieve than non-instrumental verbs for children with SLI and typically language-developing controls. In contrast, instrumental verbs with a name relation to the noun were significantly easier to name than instrumental verbs without a name relation for all groups. Children with SLI performed on par with vocabulary-matched peers. The results based on error types suggest that the greater difficulties children with SLI have with action naming is lexical-semantic in nature. The findings indicate a need to examine the link between the verb naming deficit in SLI to structural and functional abnormalities in Broca's area.
Keywords: Instrumental verbs; Instrumental verbs; Greek; Diglossia; Lemma; Lexeme; Semantic complexity